Pengaruh Pupuk Kandang Ayam dan Pupuk Hijau Calopogonium mucunoides Terhadap Pertumbuhan dan Produksi Kedelai Panen Muda yang Dibudidayakan Secara Organik - Maya Melati; Wisdiyastuti Andriyani (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
The objective of the study was to investigate the effect of chicken manure and green manure Calopogonium mucunoides on the growth and production of vegetable soybean under organic farming system. The study was conducted at IPB research station, Leuwikopo, Darmaga, Bogor from June 2004 to March 2005.  The experiment used split plot design with chicken manure dosages (0 and 10 ton/ha) as main plots and seed of green manure dosages (0, 7.5, 15, and 30 ton/ha) as sub plots. Chicken manure significantly resulted in better agronomic characters compared to that of without chicken manure. Green manure significantly increased plant height on 4 to 7 weeks after planting (WAP), number of leaves on 6 WAP. Interaction between chicken manure and green manure significantly influenced fresh weight of root nodule and 100 seeds. Fresh weight of 100 seeds was the highest with the application of either 10 ton chicken manure/ha or 15 kg seed of green manure/ha. Except plant height and number of leaves, generally growth and production of soybean under organic farming system were better than those under conventional farming   Key words: Vegetable soybean, organic farming, chicken manure, green manure, Calopogonium mucunoides